Aerodynamic and Infrared Radiation Characteristics of the Spherical Convergent Flap Nozzle under Vector Actuations. Issue 1 (1st March 2022) - Bai, Jin; Yang, Qingzhen; Li, Yiwen; Gao, Xiang
Abstract: In present work, the aerodynamic characteristics and the infrared radiation (IR) features of the spherical convergent flap nozzle (SCFN) under vector actuating operations have been studied numerically. The infrared radiation (IR) features of the nozzle under different vector actuation angle have been studied using the reverse Monte-Carlo method (RMCM). Several parameters, such as IR intensity, radiation brightness, and the spectral radiant intensity of the nozzle, are analyzed in detail. The results show that SCFN radiation intensity distribution gradually transitions from two-peak distribution to single-peak distribution. When the pitching motion is activated, the "second peak" located downstream of the deflection vector angle is gradually weakened and disappears. The peak gradually approaches the peak of the mixer, and the contribution of the mixer gradually dominates. With the increase of geometric vector angle in the pitching direction, the detection angle of the nozzle's infrared radiation intensity peak is less than the geometric vector angle, meanwhile the decrease of the peak value of the infrared radiation intensity of the nozzle is parabolic with the geometric vector angle. Along the direction of the pitching operation, the average value of the infrared radiation at a detection angle of −35° to 35° decreases linearly. When the yaw motion is activated, the infrared radiation intensity distribution in the backward direction of the nozzle exhibits a single-peak feature, and the detection angle at which the peak is located is also smaller than its geometric vector angle. Using the detection angle of the peak as the axis of symmetry, the curve of the infrared radiation intensity distribution behind the nozzle is symmetrical. As the geometric vector angle in the yaw direction increases, along the direction of the pitching operation, both the average value of infrared radiation at a detection angle of -35° to 35° and the peak value of the backward infrared integrated radiation intensity of the nozzle decrease linearly. Besides, the maximum drop is much smaller than the maximum drop during pitching operation.